Expert system for damage diagnosis on laptop using forward chaining method - Erwin Okta Resa Dwiyan (NAROTAMA UNIVERSITY, 2022)
Expert system is a computer-based system that uses knowledge. Facts and reasoning techniques in solving a problem can usually only be done by an expert in that field. In this case the author examines the damage to the laptop, the laptop is one of the computing equipment that can help humans in carrying out work, the use of laptops has increased according to needs. With the large number of users, the potential for damage to the laptop will also be greater. The problem in this research is how to write a system that can make it easier for users to diagnose damage to laptops. The method used by the author in making this expert system is Forward Chaining. The system to be built is a computer-based system. The diagnosis generated by this system is also equipped with the types of damage and symptoms on the laptop. The system will also analyze the answers to each question posed, so that diagnostic results are obtained based on the existing knowledge in this expert system.